Still Water - Stuart, Amy, 1975- (New York, New York : Simon & Schuster Audio, 2018)
Sally Proulx and her young boy have mysteriously disappeared in the stormy town of High River. Clare ODey is hired to track them down, hoping against all odds to find them alive. But High River isnt the typical town. As the truth surges through High River, Clare must face the very thing she has so desperately been running from, even if it comes at a devastating cost.
Keywords: Missing persons -- Investigation; Fiction; Drowning victims; Fiction; Secrecy; Fiction; Thrillers (Fiction); Detective and mystery fiction; Audiobooks; Audiobooks